Disiplin Kerja Tentor Pada Bimbingan Belajar Excellent Brain (e-Brain) Kabanjahe, Kecamatan Kabanjahe, Kabupaten Karo - Ingan Ukur Br Sitepu; Menanti Sembiring; Permikaria Br Ginting; Alpina Darmayanti Br Sitepu (CV. Ulil Albab Corp, 2024)
Discipline is one of the reasons on how an employee builds strong consistency in aiming to build and create progress for himself and the organization. The urgency of discipline is the level of compliance and obedience to the rules that apply and are willing to accept sanctions or punishments if they violate the rules set out in that discipline. The purpose of this service is aimed at an organization that work discipline aims to maintain a worker or employee in order and smooth implementation of work activities and tasks, to get maximum results. The method used is an interview to find solutions to problems. For this reason, for the analysis of the work discipline of the tentor at the excellent brain kabanjahe tutoring, the author wants to discuss to improve the discipline of the teacher to make it easier to carry out the performance of the teaching team, and for the teacher to feel a calm working atmosphere so that it can increase the work spirit in living his day at work.